Dry-co-grinding of doped TiO2 with nitrogen, silicon or selenium for enhanced photocatalytic activity under UV/visible and visible light irradiation for environmental applications (2019)
TiO2 doped with nitrogen (N), silicon (Si), or selenium (Se) (N-TiO2, Si-TiO2, and Se-TiO2) were obtained by the integrated sol-gel and solvothermal method with short time of crystallization and low temperature. The UV/visible and visible light absorption and photocatalytic activity of these doped TiO2 materials were improved by a dry-co-grinding process with a short grinding time and low rotational speed (30 min at 200 rpm) to obtain N-TiO2/Si-TiO2 and N-TiO2/Se-TiO2 catalysts. The materials were characterized by XRD, Raman, BET surface area and porosity, XRF, SEM, TEM, FTIR-ATR, and UV/vis-DRS analyses. The photocatalytic activity of these materials was evaluated by the degradation of phenol under UV/visible and visible light irradiation. The integrated sol-gel and solvothermal methods with short time of crystallization (2 h) and low temperature (225 °C), and the dry-co-grinding process during 30 min at 200 rpm led to materials (N-TiO2/Si-TiO2 and N-TiO2/Se-TiO2) with higher specific surface area, a reduction in the band gap value, and an enhancement of the absorption in the visible light spectrum. Moreover, N-TiO2/Si-TiO2 and N-TiO2/Se-TiO2 exhibited higher photocatalytic activities for degradation of phenol under UV/visible and visible light irradiation than those obtained with the doped TiO2, synthesized TiO2 or TiO2 P25.